Correction: Discovering atomistic pathways for supply of metal atoms from methyl-based precursors to graphene surface. Issue 7 (6th February 2023) - Sangiovanni, Davide G.; Faccio, Ricardo; Gueorguiev, Gueorgui Kostov; Kakanakova-Georgieva, Anelia
Abstract : Correction for 'Discovering atomistic pathways for supply of metal atoms from methyl-based precursors to graphene surface' by Davide G. Sangiovanni et al., Phys. Chem. Chem. Phys., 2023, 25, 829–837, ; https://doi.org/10.1039/D2CP04091C .